KAJIAN KELAYAKAN TEKNIS DAN FINANSIAL PRODUKSI NUGGET JAMUR TIRAM PUTIH (Pleurotus ostreatus) RASA IKAN TONGKOL (Euthynus aletrates) SKALA INDUSTRI KECIL - Cahyuni Novia (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2011)
Pleurotus ostreatus with Euthynus aletrates taste was one kind of Pleurotus ostreatus nugget processing which was chopped and added with Euthynus aletrates and various kinds of spices, mixed with blinding agents, formed into certain shapes and subsequently smeared with bread crumb and then freezed. Randomized Block Design was used as research method, Friedman test was used as organoleptic test, while effectivity index was used to determine the best treatments of chemical and organoleptic parameters. Break Event Point (BEP), Payback Period (PP), Net Present Value (NPV) and Profitability Index (PI) were used in calculating financial feasibility study. The result research showed the best treatment based on effectivity index was obtained from 100 g Pleurotus ostreatus, 25 g Euthynus aletrates and 15 g wheat flour with following characteristic: fat 0.69%; protein 8.80%; water activity 64.41%; ash 2.26%; carbohydrate 25.94%; taste 6.12; colour 4.88; and flavour 3.76. The feasibility analysis result in small scale industry showed the cost of goods manufactured was Rp. 5,695/250 g. Break Event Point (BEP) was reached at sales volume of 23,729 unit or Rp. 202,697,442.09. Payback Period was reached at 2 year 8 months 23 days time. Net Present Value (NPV) was Rp. 180,633,576. While the Profitability Index (PI) was 1.46 thereby this industry of nugget production from Pleurotus ostreatus with Euthynus aletrates addition was feasible.